Louisiana Romani: Constructing Race in the Colonial Caribbean - Ostendorf, Ann (Romano džaniben, 2021)
Romani experiences in the eighteenth-century French (and then Spanish) colony of Louisiana reveal how diverse evolving American racial regimes were informed by and overlapped with older European anti-Romani sentiments. Many Roma appear in Louisiana records at the crux of solidifying racial categories. Romani women who married and partnered with Black and Native American men were most consistently labeled with words that referenced their Romani heritage. Their sexual choices reveal a perception of their racial liminality that only gradually disappeared. A self-described "Boheme" man’s court testimony, the only known self-narration by a colonial Caribbean Rom, attests to his struggle to situate himself into the distinctively fluid racialized social order of Louisiana. Such choices reveal Romani attempts to engage racial categories to suit their own interests. Yet without guaranteed full membership into colonial whiteness, their subjugated position limited their possibilities. A journey across the Atlantic forced French Roma to confront, and then position themselves into, a new social order not yet detached from the one they left behind.